Characterization of HSP70 family in watermelon (Citrullus lanatus): identification, structure, evolution, and potential function in response to ABA, cold and drought stress - Wang, Xinsheng; Jin, Zhi; Ding, Yina; Guo, Meng (Frontiers in Genetics, 2023)
Watermelon (Citrullus lanatus) as a crop with important economic value, is widely cultivated around the world. The heat shock protein 70 (HSP70) family in plant is indispensable under stress conditions. However, no comprehensive analysis of watermelon HSP70 family is reported to date. In this study, 12 ClHSP70 genes were identified from watermelon, which were unevenly located in 7 out of 11 chromosomes and divided into three subfamilies. ClHSP70 proteins were predicted to be localized primarily in cytoplasm, chloroplast, and endoplasmic reticulum. Two pairs of segmental repeats and 1 pair of tandem repeats existed in ClHSP70 genes, and ClHSP70s underwent strong purification selection. There were many abscisic acid (ABA) and abiotic stress response elements in ClHSP70 promoters. Additionally, the transcriptional levels of ClHSP70s in roots, stems, true leaves, and cotyledons were also analyzed. Some of ClHSP70 genes were also strongly induced by ABA. Furthermore, ClHSP70s also had different degrees of response to drought and cold stress. The above data indicate that ClHSP70s may be participated in growth and development, signal transduction and abiotic stress response, laying a foundation for further analysis of the function of ClHSP70s in biological processes.